Truncated TEAD‐binding protein of TAZ inhibits glioma survival through the induction of apoptosis and repression of epithelial‐mesenchymal transition. Issue 10 (18th June 2019) - Zhao, Wei; Li, Li‐Wen; Tian, Rui‐Feng; Dong, Qiu‐Feng; Li, Peng‐Qi; Yan, Zhi‐Feng; Yang, Xin; Huo, Jun‐Li; Fei, Zhou; Zhen, Hai‐Ning
Abstract: Transcriptional coactivator with PDZ‐binding motif (TAZ), a Hippo pathway downstream effector, promotes tumor progression by serving as a transcriptional coactivator with TEAD. Here, we introduced a new construct which can express the TEAD‐binding domain of TAZ protein (TAZBD), and determined its antitumor effect in malignant glioma both in vitro and in vivo. We first observed that TAZ was upregulated in glioma tissues and related to malignant clinicopathologic characteristic, indicating the crucial role of TAZ during glioma progression. In U87 and U251 cells, TAZBD expression increased the proportion of apoptotic cells, and suppressed the colony formation and tumorigenicity. Further, TAZBD also decreased cell metastasis through the repression of epithelial‐mesenchymal transition. The mechanistic study showed that TAZBD suppression of glioma cells was predominantly through blocking the TAZ‐TEAD complex formation by competing with endogenous TAZ. Thus, the gene therapy of malignant glioma through blocking TAZ‐TEAD complex by TAZBD may provide a new way for the targeted therapy of glioma. Abstract : Transcriptional coactivator with PDZ‐binding motif (TAZ) is upregulated in glioma tissues and its positive expression is related to malignant clinicopathologic characteristics. The construct TAZBD, which contains TEAD‐binding domain of TAZ, can effectively block TAZ‐TEAD complex formation in glioma cells, and further reduces proliferation and migration of glioma cells, suggesting gene therapy of malignant glioma through blocking TAZ‐TEAD complex is worthy of further investigation.